2019
DOI: 10.1063/1.5092826
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of InN on epitaxial graphene using RF-MBE

Abstract: This paper reports the fabrication of InN layers on the epitaxial graphene (EG) using radio-frequency plasma-assisted molecular beam epitaxy (RF-MBE). Prior to the fabrication of InN, single crystalline EG with step and terrace structure was formed on 6H-SiC (0001) substrate in an Ar ambient by the Si sublimation method. Single crystalline epitaxial layers of InN with smooth surfaces are successfully fabricated on the EG using RF-MBE. InN layers with terrace and step structure are grown on the graphene surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…[16] Growing InN via RF molecular beam epitaxy (MBE) Ishimaru and coworkers found that the growth turns to 3D mode after the 3 rd layer is grown despite the layer by layer growth of MBE. [17] It is obvious that this few nm thick region can be indexed as cubic InN, two of the (111) type planes are marked in the image. The other lattice spacings in the 3D part can be measured on the HREM image directly and given at the marked region also 0.285 nm along the two <111> type directions, what gives perfectly the appropriate values for the cubic InN (with a = 0.49 nm).…”
Section: Bilayer Inn Is Formed Between Graphene and Sic By An Intercamentioning
confidence: 99%
See 1 more Smart Citation
“…[16] Growing InN via RF molecular beam epitaxy (MBE) Ishimaru and coworkers found that the growth turns to 3D mode after the 3 rd layer is grown despite the layer by layer growth of MBE. [17] It is obvious that this few nm thick region can be indexed as cubic InN, two of the (111) type planes are marked in the image. The other lattice spacings in the 3D part can be measured on the HREM image directly and given at the marked region also 0.285 nm along the two <111> type directions, what gives perfectly the appropriate values for the cubic InN (with a = 0.49 nm).…”
Section: Bilayer Inn Is Formed Between Graphene and Sic By An Intercamentioning
confidence: 99%
“…[ 16 ] Growing InN via RF molecular beam epitaxy (MBE) Ishimaru and coworkers found that the growth turns to 3D mode after the 3 rd layer is grown despite the layer by layer growth of MBE. [ 17 ]…”
Section: Figurementioning
confidence: 99%
“…We have recently reported the growth of InN on epitaxial graphene using radio-frequency molecular beam epitaxy (RF-MBE). 26 Dobrovolskas et al have reported that luminescence of InN is significantly improved by adding a multilayer graphene as an interlayer, which mitigates the lattice difference between the InN layer and substrate through weak van der Waals interaction between nitride and graphene layers. 27 Growth of sp 3 -bonded three-dimensional (3D) III-nitride layers directly on the sp 2 -bonded 2D graphene is challenging.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Therefore, growth of InN on EG is expected to be very promising and is a new dimension of InN research to grow high-quality film. We have recently reported the growth of InN on epitaxial graphene using radio-frequency molecular beam epitaxy (RF-MBE) . Dobrovolskas et al have reported that luminescence of InN is significantly improved by adding a multilayer graphene as an interlayer, which mitigates the lattice difference between the InN layer and substrate through weak van der Waals interaction between nitride and graphene layers …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation